Micropropagation Studies In Almond (Prunus Dulcis Mill.) Cv. ‘shalimar’ (Applied Biological Research, 2013)
Surface-sterilized forced shoots tips were inoculated on different basal media  supplemented with various combinations of growth regulators. Quality and  quantity of growth regulators and nutrient media were found crucial for culture  establishment. Optimum culture establishment was achieved on ½MS medium  containing benzylamino purine (BAP) + indole butyric acid (IBA) [0.50 + 0.1  mg L-1] where 63.33% morphogenetic response was observed. Callusing at the base of initiating cultures was minimum with BAP + IBA (0.25 + 0.01 mg L-1).  Micro-shoots from the established cultures were sub-cultured on MS media  supplemented with BAP and NAA (naphthalene acetic acid) alone or in  combination for axillary shoot proliferation. Maximum proliferated cultures  (80%) with high number of shoots explant-1(13.7) and proliferation grade (3.9)  was obtained with BAP (0.40 mg L-1) + NAA (0.01 mg L-1). BAP proved  superior to NAA during axillary shoot proliferation. Micro-shoots (10-15 mm)  from proliferated cultures were subcultured in root induction medium (MS  medium supplemented with IBA) and incubated under darkness for 10 days at  24±1oC and then transferred to root development medium (hormone-free MS  medium) and incubated under normal culture room conditions. The rooting of  micro-shoots, root length and number of roots shoot-1 were highest in treatment  IBA (1.0 mg L-1).
Keywords: Almond; in vitro propagation; micro-propagation; proliferation; shoot-tip culture